2006
DOI: 10.2478/s11756-006-0119-4
|View full text |Cite
|
Sign up to set email alerts
|

Radiometric dating of sediment records from mountain lakes in the Tatra Mountains

Abstract: Sediment cores from nine different lakes in the Tatra Mountains, collected as part of the EU funded AL:PE, MOLAR and EMERGE projects investigating natural environmental records stored in remote mountain lake sediment sequences, were dated radiometrically by 210 Pb and 137 Cs. At five sites, D lugi Staw Gasienicowy and Zielony Staw Gasienicowy on the Polish side of the Tatra Mountains and Starolesnianske pleso, Nižné Terianske pleso, and Ľadové pleso on the Slovak side of the Tatra Mountains, the cores were sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(26 citation statements)
references
References 14 publications
5
21
0
Order By: Relevance
“…Appleby & Piliposian (2006) suppose that landslips or sediment slumps most probably caused this slumps. The most significant of these events took place in the late 19 th century and it was connected with the marked peak of chironomid productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Appleby & Piliposian (2006) suppose that landslips or sediment slumps most probably caused this slumps. The most significant of these events took place in the late 19 th century and it was connected with the marked peak of chironomid productivity.…”
Section: Discussionmentioning
confidence: 99%
“…Again, category 5 had low abundance with maximum totals found at 1.5 cm in the Czarny Staw Polski core (50% of total) and at 13 and 16 cm for Nižné Terianske pleso 50% of total; Figs 7, 8). Appleby & Piliposian, 2006). In order to get more accurate sedimentation rates applicable to our data we used mean values of sedimentation rate from different cores.…”
Section: Nižné Terianske Plesomentioning
confidence: 99%
“…The successfuly analysed ancient resting eggs from the Belauer See correspond to an age range of ca. 159-195 years (Limburg & Weider, 2002), where just 33 resting eggs from six High Tatra cores correspond to this age (0 resting eggs from DlugiSt and just 1 resting egg from NTR (Appleby & Piliposian, 2006). DNA was extracted by appropriate methods for ancient DNA: the Chelex method, the Invisorb extraction KIT for ancient DNA and the IsoQuick Nucleic Acid Extraction Kit.…”
Section: Changes In Genetic Composition Of Daphnia Populationsmentioning
confidence: 99%
“…Kopáček et al showed that the modern sediments (0-1 cm layer) of the Tatra lakes are affected by atmospheric transport of pollutants, while sediment layers below a 5 cm depth represent the pre-acidification period. The average age of the 5 cm depth was 85 years (Appleby & Piliposian, 2006). The Tatra lakes have been seriously affected by atmospheric acidification since the second half of the 20 th century, when pronounced changes occurred in their chemistry (e.g., Kopáček et al, 2001bKopáček et al, , 2004a and biology (Fott et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Wathne et al (1997), Stuchlík et al (2002), and Šporka et al (2002) have published results on total concentrations of major metals and selected palaeolimnological records on sediments from four lakes in the lake district (D lugi Staw Gasienicowy, Zielony Staw Gasienicowy, Starolesnianske pleso, and Nižné Terianske pleso). Additional dated cores of sediments from other five lakes (Ľadové pleso, Veľké Hincovo pleso, Vyšné Temnosmrečinské pleso, Vyšné Wahlenbergovo pleso, and Zmarzly Staw Gasienicowy) were collected in 2001 (Appleby & Piliposian, 2006). The dating S66 J.…”
Section: Introductionmentioning
confidence: 99%